Work-hardening of dual-phase steel - Rieger, Florian (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2016)
Dual-phase steels exhibit good mechanical properties due to a microstructure of strong martensitic inclusions embedded in a ductile ferritic matrix. This work presents a two-scale model for the underlying work-hardening effects; such as the distinctly different hardening rates observed for high-strength dual-phase steels. The model is based on geometrically necessary dislocations and comprises the average microstructural morphology as well as a direct interaction between the constituents.